Dynamics of biochemical attributes and enzymatic activities of pasteurized and bio-preserved tender coconut water during storage - Pandiselvam, R.; Prithviraj, V.; Manikantan, M. R.; Beegum, P. P. Shameena; Ramesh, S. V.; Kothakota, Anjineyulu; Mathew, A. C.; Hebbar, K. B.; Maerescu, Cristina Maria; Criste, Florin Leontin; Socol, Claudia Terezia (Frontiers in Nutrition, 2022)
The potential of bio-preservatives, namely, nisin, natamycin, and polylysine, as viable alternatives to chemical preservatives for storage of tender coconut water (TCW) during refrigerated storage (5 ± 2°C) was explored. Bio-preservative treatments were carried out after optimized heat treatment (85°C for 5 min) of TCW to establish its storage characteristics. Various concentrations (up to 125 ppm) of bio-preservatives were used for the preservation, and quality parameters of resultant TCW were assessed based on physicochemical characteristics and Food and Agriculture Organization (FAO) guidelines and statistical analysis applied. Analysis of variance (ANOVA) and post-hoc test revealed that pH and overall acceptability (OA) are the major governing factors that determine spoilage of TCW (p < 0.05). Overall, the polylysine combination was found to be most effective in ensuring quality retention of TCW. It was concluded that pasteurized TCW shelf life could be extended up to 20 days using bio-preservatives.